CONTAMINATION OF IDIOMATIC ITEMS IN THE MASS MEDIA (ON THE MATERIAL OF THE CZECH LANGUAGE) - Derevianko, V. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article examines the contamination as one of the types of productive forms of actualization of idioms based on the Czech periodicals, gives the definition of contamination, analyzes the criteria of separating contamination from related phenomena, makes the classification of contamination models based on the elaborated practical material.